10th International Conference of sport kinetics, Belgrade, Serbia, 24-26 August 2007 (2007)
The Conference provides scientific knowledge and offers opportunities for discussion, exchange of ideas and experiences in the area of Human Kinetics and Sport science through a current issues and comparative perspective. International Scientific Conference "10. Sport Kinetics 2007" - 15 years Jubilee of existing International Association of Sport Kinetics Belgrade, Serbia, 24-26 August 2007. A NEW IDEAS IN FUNDAMENTALS OF HUMAN MOVEMENT AND SPORT SCIENCE: CURRENT ISSUES AND PERSPECTIVES